Well Begun, but Aiming Higher : A Review of Vietnam's Education Trends in the Past 20 Years and Emerging Challenges - Dang, Hai-Anh H.; Glewwe, Paul W. (World Bank, Washington, DC, 2017)
Given its modest position as a lower-middle-income country, Vietnam stands out from the rest of the world with its remarkable performance on standardized test scores, school enrollment, and completed years of schooling. This paper provides an overview of the factors behind this exemplary performance, from an institutional viewpoint and by analyzing several data sources, some of which have rarely been used. The study finds that Vietnam has significantly increased school enrollment at all school levels in the past 20 years, and has achieved virtually universal primary school enrollment. Girls' net enrollment rates caught up with and then overtook those of boys at the secondary level in the past decade. Most of the variation in school enrollment and completed years of schooling was due to within-commune individual factors, rather than between-commune or between-province factors. School-level factors played an important, but diminishing, role in determining students' test scores, which was likely caused by a convergence in school quality in the country. The paper further discusses a host of challenges for the country—most of which have received insufficient attention to date—such as little school choice, a low secondary enrollment rate (compared with other Programme for International Student Assessment participants), inadequate training for the labor market, and the necessity of strategic planning for systemic reforms.